Salmonella sp. Detection in Elementary School Street Foods in Surabaya - Adelia Anggasta Adzhani; Marijam Purwanta; Ivan Rahmatullah (Biomolecular and Health Science Journal, 2018)
Introduction: Street foods are food and drink which are processed on the selling spot and/or served as ready-to-consume foods by food vendors to sell to people. Foods and drinks which are rested for too long in the environment will make it possible to get contaminated by pathogen microbes and then results in disease. One of the microbes that is considerably contaminating street foods is Salmonella. We aim to identify Salmonella on drink which are offered in the canteens of Public Elementary School.Methods: This research is design as a descriptive observational, including incubation in Selenite broth, streak in MacConkey agar, and species identification using biochemical tests.Results: There were no Salmonella sp. in drinks sample of street foods which are offered both inside and outside the canteens of Public Elementary School 1 Surabaya, but other gram-negative bacteria contaminated foods.Conclusion: The street foods in elementary school, both the main ingredients and tools used during food processing and serving, still have contamination from pathogen, especially gram-negative bacteria. The vendors and sellers need to be taught how to process and serve foods in better hygiene.